Welfare of Native Goat Breeds in Serbia—Emphasis on Parasitological Infections - Nenadović, Katarina; Ilić, Tamara; Jovanović, Nemanja; Bugarski, Dejan; Vučinić, Marijana (Frontiers in Veterinary Science, 2021)
Native goat breeds in Serbia have been recognized as an important element of regional agrobiodiversity and play an important role in the safeguarding of cultural and traditional heritage. The aim of this study was to identify the main welfare issues likely to be encountered in extensive goat farming systems with an emphasis on parasitological infections. The study was conducted during the winter season on four small farms of native Balkan and Serbian white goats. For welfare assessment, animal-based indicators from the AWIN protocol for goats were used. All fecal samples for parasites were qualitatively and quantitatively examined. The main welfare issues identified were poor hair coat condition (62.79%), dirty and light soiling hindquarters (31.40%), thin body condition score (26.74%), abscesses (19.78%), and udder asymmetry (18.60%). In addition, an important and prevalent welfare problem identified across all farms was parasite infection and weak significantly (p<0.001) correlation between certain parasites (Strongylidae, Moniezia spp, Buxtonella sulcata and Protostrongylidae) and welfare indicators such as poor hair coat condition and nasal discharge. The results of this study provided the first overview and valuable insight into the impact of extensive systems on the welfare of native goats in the Balcan region.